Pediatric Surgery, Flowcharts and Clinical Algorithms - Shehata, Sameh (IntechOpen, 2019)
Pediatric Surgery, Flowcharts and Clinical Algorithms is an updated review of some common pediatric surgical problems. The authors of the chapters have made a full review of the selected topics including the basic science facts necessary for the proper understanding of conditions (anatomy, physiology and embryology), such as gastrointestinal disorders, abdominal wall defects, choledochal cysts, and others, with special emphasis on antenatal diagnosis and management.A flow chart (or management algorithm) is included to facilitate decision making in choice of the proper diagnostic tools or the most efficient surgical (or non-surgical) strategy.The book is intended for pediatric surgeons, pediatricians, and researchers in any of the topics included.